2002
DOI: 10.1148/radiographics.22.suppl_1.g02oc26s25
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Lung Anomalies in the Adult: Radiologic-Pathologic Correlation

Abstract: Encountering a developmental lung anomaly in the adult can be a challenge, as the abnormality may be mistaken for something more sinister. The common anomalies encountered are classified into three broad categories: bronchopulmonary (lung bud) anomalies, vascular anomalies, and combined lung and vascular anomalies. The imaging features of these developmental anomalies at conventional radiography, ventilation-perfusion lung nuclear scanning, angiography, computed tomography, and magnetic resonance imaging are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(136 citation statements)
references
References 45 publications
3
114
0
19
Order By: Relevance
“…During the arterial phase of the contrasted CT scan, the feeding vessel, which commonly originates from the thoracic or supraceliac abdominal aorta may become visible, allowing accurate diagnosis. 2,8,11 In our case we opted for aortic angiography. Huang et al reported on the use of Doppler sonography in the diagnosis of pulmonary sequestration in another octogenarian patient, however, they subsequently confirmed findings on CT angiography.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…During the arterial phase of the contrasted CT scan, the feeding vessel, which commonly originates from the thoracic or supraceliac abdominal aorta may become visible, allowing accurate diagnosis. 2,8,11 In our case we opted for aortic angiography. Huang et al reported on the use of Doppler sonography in the diagnosis of pulmonary sequestration in another octogenarian patient, however, they subsequently confirmed findings on CT angiography.…”
Section: Discussionmentioning
confidence: 95%
“…1 Blood supply originates from the aorta or various peripheral arteries. 1,2 It is also referred to as cystic lung disease. The intralobar type accounts for approximately 75% of cases; extralobar pulmonary sequestration accounts for 25% of cases, is located extrapulmonarily and forms its own visceral pleura.…”
mentioning
confidence: 99%
“…At expiration, 90% or more patients show signs of collapse (malacia) with or without airtrapping. Calcifications in the airway walls may be seen in approximately 40% of patients [43,44] . CT is particularly useful for the planning of interventional procedures, such as stent placement, and also for follow-up in patients undergoing anti-inflammatory treatment.…”
Section: Relapsing Polychondritismentioning
confidence: 99%
“…Pulmonary artery sling is a condition in which the left pulmonary artery arises from the right main pulmonary artery [44] . As the vessel courses to the left lung, it passes between the trachea and esophagus, giving rise to the potential compression of the trachea [53] .…”
Section: Extrinsic Tracheal Narrowingmentioning
confidence: 99%
“…Bronchial atresia is believed to result from the insufficient supply of blood to the bronchial bud during embryologic development. [6,7]. Frequently, a mucocele will develop distal to the atretic airway due to recurrent infections.…”
Section: Introductionmentioning
confidence: 99%